Who cares? Evidence on informal and formal home care use in Estonia - Irina Mozhaeva (Baltic Journal of Economics, 2019)
Despite increasing attention to long-term care (LTC) and related challenges in the Estonian social policy agenda, the distributional fairness of LTC services in the country has received very limited attention. Using SHARE data, we address informal and formal home care services and identify the socio-economic factors that drive or hinder their use among the Estonian elderly. The relationship between informal and formal home care utilization is estimated applying the new approach to instrumental variable method proposed by Lewbel [2012. Using heteroscedasticity to identify and estimate mismeasured and endogenous regressor models. Journal of Business and Economic Statistics, 30(1), 67-80]. We find that it is important to distinguish among informal care provided by household members, other relatives and non-relatives because the same socio-economic factors might differentially affect the propensity to use these kinds of care. The estimation results indicate that informal care provided by non-relatives complements formal home care. LTC policy in Estonia ensures the absence of tangible financial, ethnic and urban/rural barriers to the use of formal home care.
Keywords: C25; C26; I11; I12; I18; J14; 330; Estonia; formal home care; informal care; long-term care; SHARE